Creation Libretti: experiencing playing with sounds in Poetic Gatherings in Children Education (Orfeu, 2017)
The project “Creation Libretti: the experience of playing with sounds in Poetic Gatherings in  Childhood Education” took place in the university’s studio with the objective of pursuing ways of recording the  playful experience of language. The methodology of the Poetic Gatherings was sustained by a process of intense  purposeful interaction,  using the body as an instrument with excellent ability to move poetically to music, dance and literature, aiming at amplifying children’s and adults’ movement repertoire.  While  asserting the pedagogical relevance of group musical  encounters, realized through the  the complex process of learning  to inventively express  language, this study focuses reflectively on  sound-play. This  investigation contributes to broadening the themes addressed in musical education research, inviting regular investigation of educational curricula.
Keywords: Teacher education; Children education; Music education